HARMONISASI SISTEM HUKUM ISLAM TERHADAP DIVERSI DALAM UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Marsaid, Marsaid (Nurani, 2018)
The concept of diversion stipulated in the Republic of Indonesia Law Number 11 of 2012 concerning the Child Criminal Justice System is in accordance with the concept of diversion in Islamic law, because the concept of diversion in Islamic law and law both prioritizes accountability because a child will not subject to punishment, because there is no legal responsibility for any child until he reaches adulthood (balig). Whereas the concept of diversion in the future needs to be improved towards Republic of Indonesia Law Number 11 of 2012 concerning the Child Criminal Justice System by incorporating the principles of justice, certainty and compliance in the concept of diversion against children in conflict with the law with the aim of giving rights the same as children in general, then the government is obliged to provide formal education guarantees to children, and finally the child must receive assistance from a psychological expert. This article explores the harmonization of the Islamic legal system against diversion in the Republic of Indonesia Law Number 11 of 2012 concerning the Child Criminal Justice System.